2023
DOI: 10.1080/21645515.2022.2157164
|View full text |Cite
|
Sign up to set email alerts
|

A review of factors influencing vaccination policies and programs for older adults globally

Abstract: Policies and programs to increase vaccine coverage rates among adults 50 years of age or older are limited and vaccine uptake is often suboptimal. Our review evaluated evidence on the effectiveness and success of adult-targeted vaccination interventions and identified literature gaps. Literature was retrieved (2021) from PubMed, Embase, and Google Scholar databases. Outcomes assessed included data on an intervention’s effectiveness and impact on vaccine uptake. Interventions were characterized thematically: af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Through surveys and interviews with medical staff in different departments, we found that the reasons for not administering influenza vaccination in the case of free influenza vaccination are as follows: too busy to work and no time; not considered necessary to be vaccinated; not convinced of the safety of influenza vaccine; and allergic to influenza vaccine components. Given the above situation, through discussions among the departmental staff and review of relevant literature, 11 , 12 we summarized several measures that could improve the influenza vaccination rate of medical staff: 1. adopt incentive-type measures to reward by increasing bonuses those who receive influenza vaccination; 2. the vaccination department shall cooperate with key departments to carry out inoculation at the location of key departments within the agreed time; 3. through meetings and online communication, the department emphasized the necessity and importance of influenza vaccination for medical staff, as well as vaccine safety; 4. for those vaccinated as required, a half-day holiday will be given on the day of vaccination; 5. those who have not been vaccinated are required to report their valid reasons for not being vaccinated. However, our analysis was limited to medical staff in several critical areas at our hospital, and the effectiveness of these procedures needs to be confirmed by more medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Through surveys and interviews with medical staff in different departments, we found that the reasons for not administering influenza vaccination in the case of free influenza vaccination are as follows: too busy to work and no time; not considered necessary to be vaccinated; not convinced of the safety of influenza vaccine; and allergic to influenza vaccine components. Given the above situation, through discussions among the departmental staff and review of relevant literature, 11 , 12 we summarized several measures that could improve the influenza vaccination rate of medical staff: 1. adopt incentive-type measures to reward by increasing bonuses those who receive influenza vaccination; 2. the vaccination department shall cooperate with key departments to carry out inoculation at the location of key departments within the agreed time; 3. through meetings and online communication, the department emphasized the necessity and importance of influenza vaccination for medical staff, as well as vaccine safety; 4. for those vaccinated as required, a half-day holiday will be given on the day of vaccination; 5. those who have not been vaccinated are required to report their valid reasons for not being vaccinated. However, our analysis was limited to medical staff in several critical areas at our hospital, and the effectiveness of these procedures needs to be confirmed by more medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review including 24 studies reported that in older people effective interventions are awareness campaigns, incentives, or easier access to vaccination, and that combining interventions is probably more effective that single interventions [ 19 ]. It should be noted that all these interventions target factors that our work has identified as barriers in the poor older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of this review adds to the body of literature on effective interventions in increasing vaccination uptake rates among countries in the Asia-Pacific region. In addition to interventions that have been found to be effective in other countries in Asia-Pacific such as government-funded vaccination programs (Japan, Korea and Australia, China), provider-led education (i.e., face-to-face discussions about vaccination) (China and Hong Kong), recommendation from a provider to be vaccinated (Japan and China), and expanding vaccination sites and vaccinators that were evidenced to increase vaccination rates (Japan, Korea) [9], this review shows that using informational flyers and posters, nurse reminders, highlighting the baseline influenza vaccination rates among HCPs, and having structured health assessments could also increase vaccination uptake. The barriers and facilitators identified in this study such as perceived benefits of vaccine, perceived vaccine safety, trust, and knowledge indicates that investing in educational strategies is the key to promote vaccination uptake among older adults in Australia and Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, provider-led educational initiatives and provider recommendations were shown to be more effective than less interactive interventions, such as posters and reminder-recall letters. Interventions targeting HCPs, including awareness campaigns, incentives, affordability efforts, and vaccination site expansion also showed positive associations [9]. Both reviews above covered diverse geographical areas, however, the understanding of effective interventions at overcoming barriers related to older adults' uptake of vaccination specifically in the Asia-Pacific setting is still lacking.…”
Section: Introductionmentioning
confidence: 99%